Pengaruh Kualitas Pelayanan Dan Suasana Cafe Terhadap Kepuasan Konsumen Pada Cafe Kaloka - PUJI RAHAYU; MUHAJIRIN MUHAJIRIN; NUR KHUSNUL HAMIDAH (Journal of Innovative and Creativity, 2025)
This study aims to determine the influence of service quality and cafe atmosphere on customer satisfaction at Cafe Kaloka. Good service quality and a comfortable cafe atmosphere are two important factors that can create a positive experience for customers, which in turn impacts customer satisfaction. Customer satisfaction is a key indicator of success in service-oriented businesses, including cafes, as it contributes to customer loyalty and positive word-of-mouth recommendations. The research method used is a quantitative approach with data collection through surveys. Data were obtained from questionnaires distributed to 96 respondents who were visitors to Cafe Kaloka. This study employed multiple linear regression analysis to determine the extent of the influence of each independent variable, namely service quality and cafe atmosphere, on the dependent variable, which is customer satisfaction. The results of the analysis show that both independent variables have a positive and significant effect on customer satisfaction. Among the two, service quality was found to have a more dominant influence compared to the cafe atmosphere. This indicates that direct interaction between staff and customers plays a major role in shaping customer satisfaction. The conclusion of this study is that consistently improving service quality and creating a comfortable atmosphere can significantly enhance customer satisfaction at Cafe Kaloka. Therefore, it is recommended that the management continuously innovate in improving service quality and maintain a pleasant cafe environment to retain and increase customer loyalty.